Impact of Social Media on Information Dissemination and Public Perception during the COVID-19 Pandemic: A Scientometric Analysis - Sab M, Chaman (Journal of Data Science, Informetrics, and Citation Studies)
The study makes a bibliometric evaluation of global publications on ‘COVID-19 and Social Media” from 2020 to 2024. The published publications on this theme were searched, retrieved and downloaded from the Web of Science (WoS) citation database and analysed using bibliometric techniques based on selected bibliometrics analysis. The VOSViewer and Biblioshiny applications were used to construct indicators. The VOSviewer software and Biblioshiny applications were used to build and visualize bibliometric networks. This scientometric study examines the research output on COVID-19 and social media between 2020 and 2024, providing a comprehensive analysis of the trends collaborations and the impact of publications in this domain. A total of 1,351 documents sourced from 566 journals, books and other outlets were analysed, revealing an annual growth rate of 3.72% and an average document age of 2.03 years. Each publication garnered an average of 23.24 citations, highlighting this field's significant and scholarly impact during the pandemic. Also contributing authors, with 99 single-authored documents and a strong collaborative trend, averaging 4.55 co-authors per document. Notably, 31.24% of the work involved international collaborations, underscoring the global nature of research on the interaction of COVID-19 and social media. The analysis of document types showed that 78.5% were research articles (1,061) supplemented by 51 letters, 45 editorials and others, reflecting diverse approaches and scholarly contributions to the Keywords Plus (1,428 terms) and author-provided keywords (2,784 terms) enriched the thematic analysis. The USA leads with 475 papers and 9.718 citations, while China follows with 332 papers and 9.160 citations, The University of California system leads in volume with 35 papers (2.59% of total publications), achieving a moderate Citation-Per-Paper (CPP) of 16.09 and an h-index of 13 in contrast.
Keywords: COVID-19; Global publications; Information dissemination; Scientometrics; Social media.